2001
DOI: 10.1038/35085086
|View full text |Cite
|
Sign up to set email alerts
|

A bouquet makes ends meet

Abstract: The 'chromosomal bouquet' is a polarized chromosomal arrangement that is highly conserved among eukaryotes. There have been many hypotheses about its role in the pairing of meiotic chromosomes, but until recently these have been difficult to test.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
366
0
3

Year Published

2002
2002
2018
2018

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 377 publications
(378 citation statements)
references
References 57 publications
9
366
0
3
Order By: Relevance
“…This clustering of telomeres is thought to insure proper homolog pairing and synapsis of the homolog axes [60][61][62]. Interestingly both ATM [63] and more recently H2AX [29] have been shown to regulate the persistence of the telomere bouquet.…”
Section: Role Of H2ax In Meiosismentioning
confidence: 99%
“…This clustering of telomeres is thought to insure proper homolog pairing and synapsis of the homolog axes [60][61][62]. Interestingly both ATM [63] and more recently H2AX [29] have been shown to regulate the persistence of the telomere bouquet.…”
Section: Role Of H2ax In Meiosismentioning
confidence: 99%
“…To determine if such inactivation influences chromosomal recombination, we examined telomere clustering, synaptonemal complexes, sex bodies and chiasmata frequency in meiocytes of mTert null and control mice according to the standard procedure . It has been suggested that meiotic telomere clustering might support the alignment of homologs prior to their synaptic pairing (Scherthan 2001). We found no difference in the bouquet formation between the spermatocytes of mTert null and control mice (data not shown).…”
Section: Htert Expression Influences Telomere-nuclear Matrix Associationmentioning
confidence: 99%
“…These mechanisms of homolog association include DSB-independent pairing, meiotic recombination, synaptonemal complex formation, meiotic telomere reorganization, and an achiasmate segregation system (for review, see Roeder 1997;Kleckner 1998, 1999;Scherthan 2001;Burgess 2002;Kemp et al 2004). Elucidation of the relative contributions and interplay of these processes to accurate chromosome pairing and segregation has aided understanding of homolog associations in budding yeast.…”
mentioning
confidence: 99%